Penentuan Kebutuhan Pokok Protein Pada Napu (Tragulus napu) - Latief, Abdul (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2009)
The study aimed to determine the protein requirements for basic life and growth on Napu. Four Napus with an average 3.2 kg body weight were used in this study. 4 X 4 Latin square design was used in this research. Feed treatment were contained four levels of protein, namely 10%, 15%, 20% and 25%. Research  results showed that protein levels did not significantly affect dry matter intake, nitrogen  in faeces and nitrogen in urine. Consumption of nitrogen at levels 25% was higher (P <0.05) than 10%, 15% and 20% 0f protein level. Consumption of nitrogen on the protein level 10% and 15% were not significantly  different.  Nitrogen  balance  increased  (P  <0.05)  with  increased  levels  of  protein  in  feed. Retention of total nitrogen at the highest protein level was 0.92 g / kg BW and in the lowest level of 0.25 g/kg BW. The highest body weight gain was obtained at the protein level of 25% followed by the level of 20%, 15% and 10%. BW gain was not significantly different from the retention of nitrogen (R2= 0896). Nitrogen  requirement  was  estimated  at  the  time  of  retention  of  nitrogen  equal  to  zero  ie  0.20  g/kg BW/day, equivalent to 8.1% protein in feed. Nitrogen requirement for growth is 0.67 g N/kg BW/day, equivalent to 20.4% protein in feed